Radiographic Examination Techniques of Ossa Antebrachii In Fracture Cases With Alternative Positions at Radiology Installation of North Sumatra University’s Hospital - Rosalina, Yudica (PT Inovasi Pratama Internasional, 2023)
The antebrachial radiography examination procedure typically uses two projections, namely AP and lateral. However, at the USU General Hospital's radiology installation, radiographic examinations of the antebrachium with clinical fractures are conducted using PA and lateral projections. This study aims to determine the procedure for clinical antebrachial radiographic examination of fractures and the rationale for using PA and lateral projections. This research is qualitative, employing a case study approach. Data collection was conducted through observation, active participation, documentation, and structured interviews with radiographers, referring physicians, and radiologists. The results of the study indicate that antebrachial radiographic examinations of clinical fractures at the USU General Hospital Radiology Installation use PA and lateral projections with the elbow in a straight position. The diagnostic information produced from these examinations meets the criteria as it effectively shows both the elbow and wrist joints.